2022
DOI: 10.3390/su142315949
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Skills and Experiences Using Information and Communication Technologies in Remote Physical Education Lessons

Abstract: Information and communication technologies (ICTs) are rapidly invading education and leading to transformation in this area. During the COVID-19 pandemic, the traditional educational process was moved to a remote environment, and educators faced many challenges in maintaining the same quality as face-to-face teaching. Physical education (PE) lessons should be marked out as a special case. The aim of this research was to determine the relationship of 8–12th-grade Lithuanian students to information and communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
0
0
0
Order By: Relevance
“…Finally, regarding the health and motor skills of physical education students during the COVID-19 pandemic, the results are mixed. On the one hand, Paramitha et al [1] pointed to the health benefits of online gymnastics for adults, but on the other hand, Rutkauskaite et al [2] reported that students' physical activity decreased and their fitness deteriorated during the pandemic period. In particular, it was found that students with lower computer skills, those who spent more leisure time using ICTs, and older students were found to be less physically active and to have experienced the greatest decline in motor skills.…”
Section: Assessment Of the Results Of The Different Studiesmentioning
confidence: 99%
“…Finally, regarding the health and motor skills of physical education students during the COVID-19 pandemic, the results are mixed. On the one hand, Paramitha et al [1] pointed to the health benefits of online gymnastics for adults, but on the other hand, Rutkauskaite et al [2] reported that students' physical activity decreased and their fitness deteriorated during the pandemic period. In particular, it was found that students with lower computer skills, those who spent more leisure time using ICTs, and older students were found to be less physically active and to have experienced the greatest decline in motor skills.…”
Section: Assessment Of the Results Of The Different Studiesmentioning
confidence: 99%
“…Finally, regarding the health and motor skills of physical education students during the COVID-19 pandemic, the results are mixed. On the one hand, Paramitha et al [56] pointed to the health benefits of online gymnastics for adults, but on the other hand, Rutkauskaite et al [57] reported that students' physical activity decreased and their fitness deteriorated during the pandemic period. In particular, it was found that students with lower computer skills, those who spent more leisure time using ICTs, and older students were found to be less physically active and to have experienced the greatest decline in motor skills.…”
Section: Assessment Of the Results Of The Different Studiesmentioning
confidence: 99%
“…For example, a side effect of confinement was that it affected people's health both physically [56,58] and emotionally [52,53]. Consequences such as a sedentary lifestyle [57], weight gain [58], changes in eating and sleeping habits [65], and diseases associated with an unhealthy lifestyle have also been reported [65]. On the other hand, the efforts of the medical and sports sectors to use telemedicine and social networks to promote physical activity and the gradual return to exercise and professional sport have also been analysed [65].…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned perspective, which presents opposing viewpoints, serves to exemplify the intricate characteristics of physical education within the context of virtual learning environments. Numerous studies have provided evidence indicating that the inclusion of PE in the curriculum has a substantial impact on students' attitudes and utilization of information and communication technologies (ICT) in the educational environment (Koh et al,2022;Rutkauskaite et al,2022). The extent to which students derive enjoyment from utilizing technology for learning purposes significantly impacts their level of engagement and academic performance.…”
Section: Conceptual Frameworkmentioning
confidence: 99%